The different contributions of the eight prefrontal cortex subregions to reactive responses after unpredictable slip perturbations and vibrotactile cueing - Lee, Beom-Chan; Choi, Jongkwan; Ahn, Jooeun; Martin, Bernard J. (Frontiers in Human Neuroscience, 2023)
Recent advancements in functional near-infrared spectroscopy technology have offered a portable, wireless, wearable solution to measure activity of the prefrontal cortex (PFC) in the human neuroscience field. This study is the first to validate the different contributions made by the PFC’s eight subregions in healthy young adults to the reactive recovery responses following treadmill-induced unpredictable slip perturbations and vibrotactile cueing (i.e., precues). Our fall-inducing technology platform equipped with a split-belt treadmill provided unpredictable slip perturbations to healthy young adults while walking at their self-selected walking speed. A portable, wireless, wearable, and multi-channel (48 channels) functional near-infrared spectroscopy system evaluated the activity of PFC’s eight subregions (i.e., right and left dorsolateral prefrontal cortex (DLPFC); ventrolateral prefrontal cortex (VLPFC); frontopolar prefrontal cortex (FPFC); and orbitofrontal cortex (OFC)) as quantified by oxyhemoglobin and deoxyhemoglobin concentrations. A motion capture system and two force plates beneath the split-belt treadmill were used to quantify participants’ kinematic and kinetic behavior. All participants completed 6 trials: 2 consecutive trials without vibrotactile cueing and with a slip perturbation (control trials); 3 trials with vibrotactile cueing (2 trials with the slip perturbation (cueing trial) and 1 trial without the slip perturbation (catch trial); and 1 trial without vibrotactile cueing and with a slip perturbation (post-control trial). The PFC subregions’ activity and kinematic behavior were assessed during the three periods (i.e., standing, walking, and recovery periods). Compared to the walkers’ standing and walking periods, recovery periods showed significantly higher and lower levels of oxyhemoglobin and deoxyhemoglobin concentrations, respectively, in the right and left DLPFC, VLPFC, and FPFC, regardless of the presence of vibrotactile cueing. However, there was no significant difference in the right and left OFC between the three periods. Kinematic analyses confirmed that vibrotactile cueing significantly improved reactive recovery responses without requiring more involvement by the PFC subregions, which suggests that the sum of attentional resources is similar in cued and non-cued motor responses. The results could inform the design of wearable technologies that alert their users to the risks of falling and assist with the development of new gait perturbation paradigms that prompt reactive responses.